Od przymusu do wyboru. Młodzi dorośli a praca zdalna w czasie pandemii w podłużnych badaniach jakościowych = From coercion to choice. Young adults and remote work during the pandemic in qualitative longitudinal research - Binder, Piotr (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The analyses, inspired by boundary theory and the life course perspective, addressed the compatibility of remote work with the specificities of early adulthood. The empirical basis was a longitudinal qualitative study, i.e., 54 interviews with young adults conducted in 2020-2021. The interpretations suggest that working from home (especially hybrid work) was perceived not only as a friendly experience but also as worthwhile and desirable in the future.
Keywords: remote work; young adults; boundary theory; life course; qualitative longitudinal research; praca zdalna; młodzi dorośli; teoria granic; bieg życia; podłużne badania jakościowe